Psycho-oncology/Supportive Care in Head–Neck Cancers Patients Undergoing Radiation Therapy: A Randomized Controlled Trial - Sinha, Shwetabh; Pandey, Saket; Salins, Shirley L.; Salins, Naveen; Deodhar, Jayita; Gupta, Tejpal; Laskar, Sarbani G.; Budrukkar, Ashwini; Swain, Monali; Kumar, Anuj; Murthy, Vedang; Nair, Sudhir; Nair, Deepa; Joshi, Poonam; Chaturvedi, Pankaj; Menon, Nandini; Patil, Vijay; Joshi, Amit; Noronha, Vanita; Prabhash, Kumar; Agarwal, Jai Prakash (South Asian Journal of Cancer, 2023)
An elevated level of distress is associated with poor health-related quality of life (QoL), decreased patient satisfaction, poor treatment compliance, and possible reduced survival. This randomized trial, conducted at a single center in India, enrolled head–neck cancer patients aged > 18 years who were undergoing curative intent radiation therapy, and had significant baseline distress as per the National Comprehensive Cancer Network distress thermometer (distress score ≥ 4). The patients were randomized into the Standard arm (STD), which involved routine assessment by the oncologist, or the Interventional arm (INV), where psycho-oncology/palliative/supportive care referral was done at baseline and every week during treatment. The study's primary endpoint was the proportion of patients having significant distress 6 months' posttreatment. A total of 212 patients were randomized (n = 108 STD, n = 104 INV). At 6 months' post-treatment completion, 90 and 89 were evaluable in the STD and INV, respectively. The median distress score was 2 in both arms at this time point. There was no significant difference in the proportion of patients having significant distress in STD versus INV (9 vs. 15.6%, p = 0.20). There was an improvement in any symptom measured by the Edmonton Symptom Assessment Score (pain, tiredness, drowsiness, nausea, lack of appetite) and the QoL for the entire cohort with no statistically significant difference between arms for symptoms, QoL, or survival endpoints. Psycho-oncology and palliative/supportive care referral did not impact distress, symptom burden, QoL, or survival at 6 months' posttreatment completion significantly in this randomized trial.Clinical Trial Registry of India Registration number: CTRI/2016/01/006549.
Keywords: distress; head–neck cancer; palliative care referral; psycho-oncology referral; quality of life; supportive care